Measurement of the production cross section for Z gamma -> nu(nu)over-bar gamma in pp collisions at root s=7 TeV and limits on ZZ gamma and Z gamma gamma triple gauge boson couplings - Chatrchyan, S. (2013)
A measurement of the Z gamma -> nu(nu) over bar gamma cross section in pp collisions at root s = 7 TeV is presented, using data corresponding to an integrated luminosity of 5.0 fb(-1) collected with the CMS detector. This measurement is based on the observation of events with an imbalance of transverse energy in excess of 130 GeV and a single photon in the absolute pseudorapidity range vertical bar eta vertical bar < 1.4 with transverse energy above 145 GeV. The Z gamma -> nu<(nu)over bar>gamma production cross section is measured to be 21.1 +/- 4.2(stat.)+/- 4.3(syst.)+/- 0.5(lum.)fb, which agrees with the standard model prediction of 21.9 +/- 1.1 fb. The results are combined with the CMS measurement of Z gamma production in the l(+)l(-)gamma final state (where l is an electron or a muon) to yield the most stringent limits to date on triple gauge boson couplings. vertical bar h(3)(Z)vertical bar < 2.7 x 10(-3), vertical bar h(4)(Z)vertical bar < 1.3 x 10(-5) for ZZ gamma and vertical bar h(3)(gamma)vertical bar < 2.9 x 10(-3), vertical bar h(4)(gamma)vertical bar < 1.5 x 10(-5) for Z gamma gamma couplings.